Management Whitepaper: Innovation with Information Technologies and Using Nostalgia as an Organizational Strategy - Mojdeh Pajoutan; Chad Seifried (Journal of Applied Sports Management, 2014)
Research Problem The purpose of this paper is to show (Figure 1) how sport organizations can use innovation through information technology (IT) to support the pursuit of nostalgia by revenue-oriented sport organizations as an organizational strategy to improve or maintain their fan nation. their fan nation. A variety of organizational scholars have called for institutions and industries to be “more flexible, adaptive, entrepreneurial, and innovative to effectively meet the changing demands of today’s environment” (Sarros, Cooper, & Santora, 2008, p. 145). Within the topic of innovation , the advent of new technologies has been critically recognized as crucial for organizations to understand, accept, and devise in order to be responsive to the competitive marketplace (Hoeber & Hoeber, 2012). Further, Hoeber and Hoeber (2012) named “information technology” as one of the main driving forces for innovation and avoiding the status quo (p. 213). Can et al. (2011) notably identified a wide variety of growing IT outlets as prospective examples and causes of innovation in sports organizations. IT applications in sports stadiums, the focus of this work, were identified as applications, such as “information processing software, office automation and communication systems, photography and video combined with computer technologies, and competition intelligent equipment” to facilitate the attractiveness of sporting events progress during the course of competitions (p. 605–606). Interestingly, to our knowledge, there also have not been many papers published that address the nostalgia within the high-tech innovations of sport stadium. This is interesting, as IT innovations and their harmony with nostalgia are highly important for positioning of revenue sport organizations in the competitive sport marketplace (Seifried & Meyer, 2010). The unique features of revenue-based sport organizations were described by Seifried and Meyer (2010) as “fertile locations for nostalgia” because supporters have many memories with facilities, sports teams and so on (p. 54).